Pengembangan media audio visual terhadap pemahaman konsep IPAS kelas 5 SDN 247 Palembang - Siti Safira Asyasiah; Lukman Hakim; Lefudin (IKIP Siliwangi, 2026)
This study aims to develop audio-visual media in learning Natural and Social Sciences (IPAS) for fifth grade elementary school students that are valid, practical and have a potential effect on improving students' conceptual understanding. The background of this study is based on the difficulties often experienced by teachers and students in conveying and understanding abstract and complex IPAS concepts, such as the material